TINGKAT HARMONI SOSIAL SISWA SMP SE- KOTA PONTIANAK - Halida, Halida; Yuline, Yuline; Fergina, Ana; Putri, Amallia; Dewantara, Jagad Aditya; Borneo, Zaky Ibrahim Zayn (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the level of social harmony in both female and male students of class VII SMP in Pontianak City. This type of research uses quantitative research, and the population is class VII students of SMPN in Pontianak City. The sampling technique was carried out by using a random sampling technique. Data collection is using a social harmony questionnaire distributed via a google form. The method used is descriptive, aiming to describe social harmony accurately, clearly, detailed, and systematically. The analysis technique used is a descriptive statistical analysis using the mean, median, frequency, standard deviation, range, mode, and ability. The social harmony of four indicators: awareness of cultural diversity, tolerance, self-disclosure, and conflict resolution constructively. The results showed that students' average social harmony score was 139, 47. Social harmony for each indicator, the average is on 50%. This study suggests conducting correlation research to see the connectedness of social peace with family, cultural, religious, and socio-economic status.